Islamic Epistemology in the Socialization of Islamic Sharia and the Implementation of Democracy in Indonesia - Harisah, Afifuddin; Irawan, Andi Muhammad; Iskandar , Iskandar (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This paper discusses the importance of the formulation and dissemination of the epistemology of Islam in order to build nationalism in the implementation of Islamic laws and democracy in Indonesia. The national insight that is multidimensional and multicultural based on Islamic epistemology reasoning, is requisite and needs to be disseminated in the Islamic education domain in all levels of the institution. The descriptive analysis used in this paper reveals that the implementation of Islamic laws in society, especially in Indonesia, requires rationalization of laws, either those that have been applied or will be applied. This is necessary to ensure the existence and the role of religion in finding the solution to various problems faced by society. In politics, Islam recognizes democracy as a system imported from western countries. In normative and theoretical domains, democracy can be employed as a social-political system that is able to embody the principles of equality (al-musawah), freedom (al-hurriyyah), public accountability (al-mas’uliyah), and people sovereignty (al-aghlabiyyah).